2001
DOI: 10.1046/j.1471-4159.2001.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for non‐oxidative dopamine cytotoxicity: potent activation of NF‐κ B and lack of protection by anti‐oxidants

Abstract: A stable aromatic acid decarboxylase expressing the Chinese hamster ovary cell line was developed to study the cytotoxic properties of intracellular and extracellular dopamine. The relative impermeability of cells to dopamine, but not to L-DOPA, allows the differentiation of extracellular and intracellular dopamine cytotoxicity. In contrast to extracellular dopamine, intracellular dopamine toxicity was resistant to antioxidant protection, and did not require melanin formation for its toxicity. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
1
19
0
2
Order By: Relevance
“…In addition, apoptosis induced via a mitochondria-dependent cascade involving the activation of caspase-9 and the apoptosome complex is enhanced in cerebral cortex from VMAT2 deficient mice during early postnatal developmental (P1-P3) (Stankovski et al, 2007). Even though apoptotic mechanisms underlying dopamine dysregulation is not the focus of this paper, it has been shown by others that the stress-inducible transcription factor NF-kappa B can be activated by intracellular dopamine, a process resistant to antioxidant protection (Weingarten et al, 2001). In this way, a low expression of VMAT2 could trigger apoptotic cascades via the increase in cytosolic dopamine.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, apoptosis induced via a mitochondria-dependent cascade involving the activation of caspase-9 and the apoptosome complex is enhanced in cerebral cortex from VMAT2 deficient mice during early postnatal developmental (P1-P3) (Stankovski et al, 2007). Even though apoptotic mechanisms underlying dopamine dysregulation is not the focus of this paper, it has been shown by others that the stress-inducible transcription factor NF-kappa B can be activated by intracellular dopamine, a process resistant to antioxidant protection (Weingarten et al, 2001). In this way, a low expression of VMAT2 could trigger apoptotic cascades via the increase in cytosolic dopamine.…”
Section: Discussionmentioning
confidence: 94%
“…Excess dopamine may also be a potent pro-oxidant or a neurotoxic agent via non-oxidative pathways (Luo et al 1999; Hattori et al 1998), and its enzymatic or non-enzymatic oxidation yields redox-active free radicals and the robust pro-oxidant dopamine-quinones and semiquinones which may generate tetra-hydroisoquinones that generate even more dopamine-induced oxidative stress (Vallone, Picetti, Borelli 2000). Finally, dopamine may be oxidized Weingarten, Bermak, Zhou 2001; Pedrosa and Soares-da-Silva 2002), boosting its neuronal killing potential, provoking univalent reduction of oxygen and consequent production of superoxide anion, hydrogen peroxide, and hydroxyl radical (Bindoli, Rigobello, Deeble 1992). Moreover, as the non-catalyzed, physiological oxidation of dopamine is slow, free-transition metal ions like iron and manganese may accelerate its oxidation via biochemical processing mentioned above (Lloyd 1995; Jimenez et al 1993), closing a cycle that we may label as an “oxi-dopamatergic cascade” (oxidation-glutamate-dopamine oxidative stress).…”
Section: Psychosocial Stress-anxiety-depression and Oxidative Stressmentioning
confidence: 99%
“…Purified D2R couples to the heterotrimeric G proteins G i 1, G i 2, and G i 3, and preferably activates G i 2 (Senogles et al, 1990), whereas in the brain, D2R preferentially couples to G o (Jiang et al, 2001). Several investigators recently reported that dopamine could induce NF-B activation in PC12, Jurkat, and Chinese hamster ovary cells, and contributes to regulation of apoptosis (Luo et al, 1999;Lee et al, 2001;Panet et al, 2001;Weingarten et al, 2001) and expression of HIV-1 genes (Rohr et al, 1999). However, the specific receptors and the underlying signaling mechanisms for this activity have not been characterized.…”
mentioning
confidence: 99%